ESPAÇOS VERDES URBANOS PÚBLICOS DE CAMPO GRANDE (MS), NO CONTROLE DE ÁGUAS PLUVIAIS: AVALIAÇÃO DO SERVIÇO ECOSSISTÊMICO DE REGULAÇÃO - PRISCILLA AZAMBUJA JUSTI (2024)
The increase in population in urban areas and the growing sensitivity to adverse events caused by climate change lead those responsible for public management to seek alternative technical tools that contribute to the sustainable and integrated functioning of the city, ensuring the quality of life of its residents and visitors. Urban green spaces, which integrate a set of green urban areas and vegetation, are presented as natural or even artificial environments to improve urban environmental quality. It is highlighted here that these environments benefit the mitigation of surface runoff and flooding. In turn, the use of indicators, as sustainable urban management tools, allows the monitoring and evaluation of public urban green spaces, in the control of urban rainwater. And as technical tools, the applicability of indicators contributes to sustainable urban planning and decision-making by public managers with a view to designing public policies that meet the dimensions of sustainability. The situation in Campo Grande (MS) is no different. The city is also in the process of urbanization and is experiencing the effects of climate change, especially related to extreme hydrological events, in the urban environment. This requires actions from the municipal government, adaptation techniques, or even resolution to definitively solve the problem. From this perspective, this research aims to answer the following question that arises as a central question: What is the efficiency of ecosystem services, provided by public urban green spaces, in Campo Grande (MS), in controlling rainwater? Thus, the general objective of this proposal is to evaluate the efficiency of ecosystem services, provided by public urban green spaces, in Campo Grande (MS), in controlling rainwater. This is a descriptive and exploratory research, to be based on a systematic bibliographic review, based on the collection and use of primary and secondary data. It will adopt a mixed approach to the research object. As expected, it is projected that the results can verify whether public urban green spaces, established in Campo Grande (MS), are sufficient to mitigate extreme hydrological events. The study evaluated 70 public urban green spaces in Campo Grande (MS), applying the CN method to analyze surface runoff and considering parameters such as average CN, green area index (IAV) and two NBR indicators, and through Principal Component Analysis. In addition to proposing improvements, such as afforestation and drainage materials, highlighting the need to increase public urban green spaces in some neighborhoods for effective rainwater management, and highlighting the importance of joint analysis of indicators in sustainable urban planning.